Autonomy movements and federal India - Bhupinder Singh (Jaipur : Rawat Publications, 2002)
On the autonomy movements occuring in various states of India after 1947.
Includes index.
Keywords: India -- History -- Autonomy and independence movements; India -- Politics and government -- 1947-